ANALISIS PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN TEMATIK KELAS TINGGI DI SDN 06 PONTIANAK SELATAN - Izha Tri Idani Ningsi; Hery Kresnadi; Asmayani Salimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe how audio visual media is used in high-class thematic learning at SDN 06 South Pontianak. This research includes descriptive qualitative research, namely data collection conducted using observation, interview, and documentation methods. Data analysis using qualitative descriptive analysis, namely in the form of written data or from interviews from related parties. The results of the research are as follows: Based on research that has been done at SD Negeri 06 Pontianak Selatan related to the use of audio visual media in thematic learning in the High Class of SD Negeri 06 Pontianak Selatan, there are sections that are appropriate and not yet appropriate, with the steps and characteristics of media use. The appropriate part is in the steps to use audio visual media. On the thematic learning characteristics the appropriate part is student-centered, presenting concepts from various subjects, providing firsthand experience and using the principles of learning while playing and enjoyable. The part that is not suitable is, in the separation of the subjects is not so clear, the results of learning in accordance with the interests and needs of students , and is flexible.Keywords: Audio Visual Media, High Class, Thematic Learning